Resources, Rent Diversification, and the Collapse of Autocratic Regimes. (December 2015) - Fails, Matthew D.; DuBuis, Marc C.
A growing literature demonstrates that "unearned income"—such as that which stems from natural resources—stabilizes authoritarian regimes. In this paper, we refine this argument to emphasize not just the volume of these rents but also their diversity and the extent to which they can act as substitutes for one another. Specifically, a greater number of distinct sources of rents, and a more equitable distribution among them, provide an important hedge against any sudden change in the ability of autocracies to capture these rents and should lead to more stable regimes. We use a procedure from the literature on market concentration to develop a single measure, termed rent diversification, which captures these characteristics. We then use this new measure in a quantitative analysis examining the likelihood of regime failure. Our findings provide strong evidence that autocracies with more diversified rent portfolios are much less likely to collapse.